2019
DOI: 10.1007/s11356-019-04719-9
|View full text |Cite
|
Sign up to set email alerts
|

Does plant species selection in functional active green walls influence VOC phytoremediation efficiency?

Abstract: Volatile organic compounds (VOCs) are of public concern due to their adverse health effects. Botanical air filtration is a promising technology for reducing indoor air contaminants, but the underlying mechanisms are not fully understood. This study assessed active botanical biofilters for their single-pass removal efficiency (SPRE) for benzene, ethyl acetate and ambient total volatile organic compounds (TVOC)s, at concentrations of in situ relevance. Biofilters containing four plant species (Chlorophytum orchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 40 publications
1
29
1
Order By: Relevance
“…As the mixture of VOC species and quantity of emitted VOCs varies amongst different plant species [59], it is possible that differences in biogenic VOC emissions between the S. wallisii and S. podophyllum biofilters may have contributed to the interaction between light type and botanical biofilter species, influencing the rate of NO 2 decay. Additionally, botanical biofilters are also capable of filtering out a range of VOCs [33] and the degree to which various VOCs are filtered is dependent on the plant species present within the biofilter [35]. These traits may have also differentially influenced the VOC concentration profile within the flow reactor and therefore, it is possible that the VOC profile associated with each plant species may have had ramifications for the NO 2 decay rate constants of each of the botanical biofilters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the mixture of VOC species and quantity of emitted VOCs varies amongst different plant species [59], it is possible that differences in biogenic VOC emissions between the S. wallisii and S. podophyllum biofilters may have contributed to the interaction between light type and botanical biofilter species, influencing the rate of NO 2 decay. Additionally, botanical biofilters are also capable of filtering out a range of VOCs [33] and the degree to which various VOCs are filtered is dependent on the plant species present within the biofilter [35]. These traits may have also differentially influenced the VOC concentration profile within the flow reactor and therefore, it is possible that the VOC profile associated with each plant species may have had ramifications for the NO 2 decay rate constants of each of the botanical biofilters.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported that green wall systems, in particular active green walls, have a high capacity to phytoremediate several air pollutants including particulate matter (PM) [30,31] and VOCs [32,33]. Regarding green wall VOC removal, biodegradation of VOCs by the rhizospheric bacteria along with substrate adsorption are considered as the primary sinks for VOC removal [24,34], however, plant-associated effects also play a role in VOC removal [35]. In the current experiment, all treatments contained both plants and substrate as discriminating between the substrate and plant effects are of no interest in practical applications of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of VOC and PM removal efficiencies, a flow through chamber was used, previously described in Irga et al (2019). In brief, the modules were placed in a sealed Perspex chamber (0.6 m 3 ; 216 L).…”
Section: Single Pass Removal Efficiency Chambermentioning
confidence: 99%
“…To determine the native species VOC removal capacity the same method described in Irga et al (2019) was applied. In brief, gaseous benzene was used as the VOC in this experiment (solubility at 25 °C = ~ 1/71 g/L).…”
Section: Voc Trialsmentioning
confidence: 99%
See 1 more Smart Citation